India-China Relations: Conflict and Cooperation in Indo-Pacific Region - Balwinder Singh (Journal of Political Studies, 2018)
From the last three decades, the Indo-Pacific has been a central theme in the global geopolitical scenario. India, China, and several other rising powers have shifted the balance of power. Thus, Indo-Pacific region marks instability and uncertainty especially caused by consistent crises of the world economy. In the present globalized era, both India and China are paramount drivers of the global economy. They are simultaneously reacting to this shifted balance of power in Indo-Pacific region. The actions of China and India towards each other and especially in Indo-Pacific region have significantly changed in last decades. At present, the Indian government has started to focus on Indo-Pacific region. The Trump Administration has focused India to contain China in Indo-Pacific region. At that moment, the Indo-Pacific region has thus become more important region than ever before. The geo-strategic significance of the Indo-Pacific region has attracted the main global-powers to preserve their strategic interests in this region. So, the Indo-Pacific has got enormous significance in the present context. From the last few years, the region has got international acknowledgment. The US`s Asia-pivot policy and China’s ‘String of Pearl’ policy have been focusing on India. The geopolitical importance of the Indo-Pacific region has dragged the western powers to counterweight growing Chinese power. That’s why; Indo-Pacific has shaped the new subject of divergence between China and India. Yet, there is no need to undermine the enlarging economic relations between the two big nations of Asia. This study also examines that how US and Pakistan are affecting the bilateral India-China relations. The study observes that how India and China satisfying their strategic interests in the Indo-Pacific region. Thus, the study tries to find out the new issues of cooperation and conflict between the two nations. Thus, the study tries to find out the new issues of cooperation and conflict between the two nations.